Configuration of frontal sinuses: A forensic perspective - Jhansi Lakshmi Suman (Journal of Pharmacy and Bioallied Sciences, 2016)
Background: Identification of an individual whether living or deceased is of paramount importance in maintaining the integrity of the society. A simple, reliable, and efficacious method always finds a way for easier acceptance and inclusion in any discipline. Likewise, identification of an individual using the radiographic frontal sinus patterns is a simple technique which emphasized to conduct the study with a proven result. Objective: The objective of the study is to evaluate the radiographic configurations of frontal sinuses for their uniqueness based on different parameters. Study Group and Methods: Study group consisted of thirty individuals (15 males and 15 females) of age between 20 and 30. Individuals with the history of sinusitis, surgery, or any trauma were not included in the study. Paranasal sinus views were taken using standard exposure parameters, and the radiographs were assessed for their uniqueness. Results: The radiographs were assessed for area size, area asymmetry, superiority of the upper border, outline of the upper border, presence or absence of partial septa and supraorbital cells, and based on these results, a unique code number was assigned to each individual to prove the uniqueness. Conclusion: A frontal sinus comparison is particularly useful when no other means of an individual identification are available. Caution must be taken regarding the physiological and pathological changes (trauma, infection, old age, surgery, etc.) and postmortem changes and about the technical issues while taking a radiograph (distance, angle, orientation of the skull). In spite of all these issues, the configuration of frontal sinus is an excellent individualizing feature.